Magnet Dislocation: An Increasing and Serious Complication Following MRI in Patients with Cochlear Implants - Hassepass, F.; Stabenau, V.; Arndt, S.; Beck, R.; Bulla, S.; Grauvogel, T.; Aschendorff, A. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Purpose: Cochlear implantation (CI) represents the gold standard in the treatment of children born deaf and postlingually deafened adults. Initial magnetic resonance imaging (MRI) was contraindicated in CI users. Meanwhile, there are specific recommendations concerning MRI compatibility depending on the type of CI system and the device manufacturer. Some CI systems are even approved for MRI with the internal magnet left in place. The aim of this study was to analyze all magnet revision surgeries in CI patients at one CI center and the relationship to MRI scans over time.Materials and Methods: Between 2000 and 2013, a total of 2027 CIs were implanted. The number of magnet dislocation (MD) surgeries and their causes was assessed retrospectively.Results: In total 12 cases of MD resulting from an MRI scan (0.59 %) were observed, accounting for 52.2 % of all magnetic revision surgeries. As per the labeling, it was considered safe to leave the internal magnet in place during MRI while following specific manufacturer recommendations: MRI intensity of 1.5 Tesla (T) and compression head bandage during examination.Conclusion: A compression head bandage in a 1.5 T MRI unit does not safely prevent MD and the related serious complications in CI recipients. We recommend a Stenvers view radiograph after MRI with the internal magnet in place for early identification of MD, at least in the case of pain during or after MRI examination. MRI in CI patients should be indicated with restraint and patients should be explicitly informed about the possible risks. Recommendations regarding MRI compatibility and the handling of CI patients issued with MRI for the most common CI systems are summarized.Key Points:• MRI in CI patients: manufacturer recommendations must be followed.• Magnet dislocation due to MRI is a serious complication.• In case of suspected magnet dislocation: Use Stenvers view radiograph for diagnosis.• Instant presentation to a CI center is mandatory for proper management of dislocation.• Immediate CI revision surgery must be performed in the case of magnet dislocation.Citation Format:• Hassepass F, Stabenau V, Arndt S et al. Magnet Dislocation: An Increasing and Serious Complication Following MRI in Patients with Cochlear Implants. Fortschr Röntgenstr 2014; 186: 680 – 685
Keywords: head/neck; MR imaging; conventional radiography; instrumentation; safety